2014
DOI: 10.1111/jeb.12320
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance evolves more frequently in C4 grass lineages

Abstract: Salt tolerance has evolved many times in the grass family, and yet few cereal crops are salt tolerant. Why has it been so difficult to develop crops tolerant of saline soils when salt tolerance has evolved so frequently in nature? One possible explanation is that some grass lineages have traits that predispose them to developing salt tolerance and that without these background traits, salt tolerance is harder to achieve. One candidate background trait is photosynthetic pathway, which has also been remarkably l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 41 publications
(63 reference statements)
0
29
0
Order By: Relevance
“…Despite this phylogenetic effect, the transition to C 4 physiology was still accompanied by changes in the ecological niche. Ancestral state reconstructions show that C 4 evolution in grasses led to consistent shifts into drier and more seasonal niche space (Edwards & Smith, ), and that C 4 grasses are more likely to migrate into arid or saline habitats than their C 3 counterparts (Osborne & Freckleton, ; Bromhan & Bennett, ). These results suggest that C 4 photosynthesis facilitates adaptation to conditions of low soil water potential, probably through the continuous adaptation of stomatal conductance and plant hydraulics, and thereby allows plants to more readily access dry niche space (Edwards & Donoghue, ; Fig.…”
Section: Contingency and The Ecological Diversity Of C4 Plantsmentioning
confidence: 99%
“…Despite this phylogenetic effect, the transition to C 4 physiology was still accompanied by changes in the ecological niche. Ancestral state reconstructions show that C 4 evolution in grasses led to consistent shifts into drier and more seasonal niche space (Edwards & Smith, ), and that C 4 grasses are more likely to migrate into arid or saline habitats than their C 3 counterparts (Osborne & Freckleton, ; Bromhan & Bennett, ). These results suggest that C 4 photosynthesis facilitates adaptation to conditions of low soil water potential, probably through the continuous adaptation of stomatal conductance and plant hydraulics, and thereby allows plants to more readily access dry niche space (Edwards & Donoghue, ; Fig.…”
Section: Contingency and The Ecological Diversity Of C4 Plantsmentioning
confidence: 99%
“…However, these investigations are biased by differences among phylogenetic groups (Taub ), and recent interspecific comparisons accounting for phylogenetic structure have revolutionised our understanding of C 4 evolutionary ecology (reviewed in Christin & Osborne ). In particular, phylogeny‐based analyses have shown that C 4 photosynthesis evolved in groups of grasses inhabiting warm regions and facilitated shifts into drier and more saline habitats (Osborne & Freckleton ; Edwards & Smith ; Bromham & Bennett ). However, the photosynthetic transitions investigated in these analyses occurred many millions of years ago and there is often a gap of several million years between C 3 and C 4 nodes in species phylogenetic trees (Christin et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that C4 plants are more like to be tolerant to different abiotic stresses (Bromham and Bennett, 2014).…”
Section: Introductionmentioning
confidence: 99%